Inwestycje komunalne jako czynnik rozwoju lokalnego - Telka, Krzysztof (Commune Investments as a Factor of Local Development, 2006)
Local authorities are currently facing qualitatively new challenges evolving from free market economy conditions and regulations connected with Poland's accession to the EU. The authorities' task in encouraging development processes is creating the possibility of a stable, harmonious and dynamic development of local societies. One of the most effective tools of affecting local development is municipal investment. Scarce of finance resources is not the only limitation to undertaking and executing investment processes. There is not a simple relationship between incomes and investment expenses or financial situation of communes, either. A special role is appointed to investments in technical as well as, gaining more and more significance, social infrastructure. The scale of voivod-ship does not always reflect real processes, including social and economic development processes, and phenomena appearing in local life. The research on communes in Radom's region is to describe the effects of local development processes and show the influence of municipal investment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 327-340